2010
DOI: 10.1358/mf.2010.32.1.1428742
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Fas and FasL expression in nicotine-induced apoptosis of endothelial cells

Abstract: Although smoking-related coronary vascular disease is well documented, the effects of nicotine have not been fully investigated. There is controversy over reports about the effect of nicotine on apoptosis. The effect of nicotine on apoptosis of human umbilical vein endothelial cells (HUVECs) and the expressions of Fas/Fas ligand (FasL) and caspase-3 were evaluated in this study. Annexin V fluorescein isothiocyanate and propidium iodide double staining demonstrated that nicotine (0.2 microM, 0.5 microM and 1 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Smoking can both increase and decrease apoptosis, depending on the cell types [ 23 , 24 ]. It was reported that smoking increases the levels of Fas (CD95) and CD4 T-cells that make cells more vulnerable to apoptosis, leading to high levels of cellular debris, which may not be adequately cleared in autoimmune diseases [ 23 ].…”
Section: The Effect Of Smoking On the Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Smoking can both increase and decrease apoptosis, depending on the cell types [ 23 , 24 ]. It was reported that smoking increases the levels of Fas (CD95) and CD4 T-cells that make cells more vulnerable to apoptosis, leading to high levels of cellular debris, which may not be adequately cleared in autoimmune diseases [ 23 ].…”
Section: The Effect Of Smoking On the Immune Systemmentioning
confidence: 99%
“…Smoking can both increase and decrease apoptosis, depending on the cell types [ 23 , 24 ]. It was reported that smoking increases the levels of Fas (CD95) and CD4 T-cells that make cells more vulnerable to apoptosis, leading to high levels of cellular debris, which may not be adequately cleared in autoimmune diseases [ 23 ]. Bijl et al reported that smoking was associated with an increase in the percentage of Fas-expressing CD4+ T and B lymphocytes; however, there were no differences between smokers and non-smokers in in vitro Fas-induced apoptosis and the percentages of circulating apoptotic lymphocytes between smokers and non-smokers [ 24 ].…”
Section: The Effect Of Smoking On the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Last but not least, smoking elevates the levels of Fas (CD95) and CD4 T-cells, making cells more prone to apoptosis. This heightened susceptibility to apoptosis results in increased levels of cellular debris, which might not be sufficiently eliminated in autoimmune disorders 37 . Smoking influences the immune system, resulting in diminished natural killer cells, suppressed hormonal cells, and cell-mediated immunity, along with the induction of dysfunction in T lymphocytes [38][39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%